BUSINESS JUDGEMENT RULE OLEH DIREKSI PERSEROAN - Isfardiyana, Siti Hapsah (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
A directors are required to have a standard of integrity and loyalty is high, appearing and acting in the interests of the company's bona fides. However, such losses can not be directly held accountable to the board of directors only for the reason wrong in deciding (mere error of judgment). Directors can be detached from the personal liability of directors if it can prove that the directors have applied the doctrine of the business judgment rule which has been carrying out its duties properly in accordance with the principles of a viable business. Thus, the directors can be detached from accountability for breach of fiduciary duty where the directors can prove negligence or fault that caused the damages is still within certain limits and tindakannnya is not for personal gain.